Sustainability Under ESG Uncertainty: Digital Capability, GreenInnovation, and Environmental Tax Pressure - Salsabila Nur Aini; Umatun Markhumah (Inovasi Analisis Data, 2026)
Purpose—This study aims to examine how sustainability uncertainty influences environmental sustainability performance through organizational capability development and regulatory pressure, with particular emphasis on the mediating role of green investment intention. It seeks to clarify how firms strategically respond to sustainability uncertainty by leveraging digital capability and green innovation to enhance sustainability outcomes.Design/methodology/approach—A quantitative research design was employed using survey-based data and analyzed through partial least squares structural equation modelling (PLS-SEM). The proposed framework integrates sustainability uncertainty, digital sustainability capability, green innovation capability, and environmental tax pressure to explain environmental sustainability performance, while explicitly testing the mediating mechanism of green investment intention.Findings—The results indicate that sustainability uncertainty exerts a negative effect on environmental sustainability performance. In contrast, digital sustainability capability and green innovation capability significantly enhance sustainability outcomes. Environmental tax pressure also contributes positively, though its effectiveness depends on firms’ internal strategic orientation. Importantly, green investment intention plays a central mediating role, translating organizational capabilities and policy pressure into improved environmental performance.Originality/value—This study advances sustainability research by integrating uncertainty theory with capability-based and investment-oriented perspectives. It provides novel empirical evidence on the mediating role of green investment intention, offering a nuanced understanding of how firms navigate sustainability uncertainty to achieve stronger environmental performance.